2011
DOI: 10.1128/jvi.00533-11
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of a Nucleotide Analog on Infectious Salmon Anemia Virus Infection

Abstract: The infectious salmon anemia virus (ISAV), which belongs to the Orthomyxoviridae family, has been responsible for major losses in the salmon industry, with mortalities close to 100% in areas where Atlantic salmon (Salmo salar) is grown. This work studied the effect of ribavirin (1-␤-D-ribofuranosyl-1,2,3-triazole-3-carbaxaide), a broad-spectrum antiviral compound with proven ability to inhibit the replicative cycle of the DNA and RNA viruses. The results show that ribavirin was able to inhibit the infectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…The cells were fixed, and cell sections were blocked with 3% bovine serum albumin (BSA) containing 0.5% Tween 20 for 30 min at 37°C (25). A monoclonal antibody against the ISAV nucleoprotein (clone 2C2/H4; Grupo Bios, BiosChile) diluted 1:500 in 1ϫ PBS and 3% BSA (26) was incubated overnight at 4°C, detected by using a goat anti-mouse antibody conjugated with Alexa Fluor 568 (Life Technologies, USA) diluted 1:1,000 in 1ϫ PBS and 3% BSA, and incubated for 1 h at room temperature. For wheat germ agglutinin (WGA) depiction, samples were stained with 5 g/ml Alexa Fluor 488-conjugated WGA (Invitrogen, USA) for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were fixed, and cell sections were blocked with 3% bovine serum albumin (BSA) containing 0.5% Tween 20 for 30 min at 37°C (25). A monoclonal antibody against the ISAV nucleoprotein (clone 2C2/H4; Grupo Bios, BiosChile) diluted 1:500 in 1ϫ PBS and 3% BSA (26) was incubated overnight at 4°C, detected by using a goat anti-mouse antibody conjugated with Alexa Fluor 568 (Life Technologies, USA) diluted 1:1,000 in 1ϫ PBS and 3% BSA, and incubated for 1 h at room temperature. For wheat germ agglutinin (WGA) depiction, samples were stained with 5 g/ml Alexa Fluor 488-conjugated WGA (Invitrogen, USA) for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…At day 7 postinfection, ASK cells infected with rISAV S6-EGFP-HPR from each passage of the recombinant virus were analyzed by confocal microscopy using the procedures described by RivasAravena et al (46). The fixed cells were observed with an LSM 510 (Zeiss) confocal microscope with the LSM image browser program to detect rISAV S6-EGFP-HPR by EGFP fluorescence.…”
Section: Analysis Of Risav S6-egfp-hpr Vrna By Rt-pcr and Qrt-pcr Tomentioning
confidence: 99%
“…The fixed cells were observed with an LSM 510 (Zeiss) confocal microscope with the LSM image browser program to detect rISAV S6-EGFP-HPR by EGFP fluorescence. In addition, rISAV was detected by monoclonal anti-HE (BiosChile) as previously described (46).…”
Section: Analysis Of Risav S6-egfp-hpr Vrna By Rt-pcr and Qrt-pcr Tomentioning
confidence: 99%
“…Samples of fish were taken at this point to evaluate the initial levels of transcripts (day 0). Then, 168 fish were treated with 6.5 mol of ribavirin/kg of fish for 10 days in the feed, in duplicate farming tanks as described (Rivas-Aravena et al, 2011). After that, the fish were fed without ribavirin.…”
Section: Treatment Of Atlantic Salmon With Ribavirinmentioning
confidence: 99%
“…In fish, it has been reported that some viral infections are inhibited by ribavirin. In particular, infections with viral hemorrhagic septicemia virus (VHSV) (Marroqui et al, 2007), chum salmon reovirus (CSV) (DeWitte-Orr and Bols, 2007), infectious pancreatic necrosis virus (IPNV) (Jashés et al, 1996;Migus and Dobos, 1980), infectious hematopoietic necrosis virus (IHNV) (Hudson et al, 1988) and infectious salmon anemia virus (ISAV) (Rivas-Aravena et al, 2011) have been shown to be dramatically reduced by ribavirin.…”
Section: Introductionmentioning
confidence: 99%